The age of commodity water privation in southern Africa - edited by David A. Mcdonald (New York Earthscan, 2005)
As globalization and market liberalization march forward unabated the global commons continue to be commodified and privatized at a rapid pace. In this global process, the ownership, sale and supply of water is increasingly a flashpoint for debates and conflict over privatization, and nowhere is the debate more advanced or acute than in Southern Africa. The Age of Commodity provides an overview of the debates over water in the region including a conceptual overview of water 'privatization', how it relates to human rights, macro-economic policy and GATS. The book then presents case studies of important water privatization initiatives in the region, drawing out crucial themes common to water privatization debates around the world including corruption, gender equity and donor conditionalities. This book is powerful and necessary reading in our new age of commodity.
Includes index
Keywords: Water